A review on the bolted flange looseness detection method - Mohd Padzly, Radzi; Mohd Hafizi, Zohari (Springer Science and Business Media Deutschland GmbH, 2023)
Early detection of bolted flange looseness in oil and gas industries is vital, as it may lead to severe problems such as leakage and explosion. The implications of this problem are not only focused on the system itself but the surrounding circumstances and coupled with the enormous economic losses associated with such failures. The use of bolts in flange structure itself can cause significant deficiencies or damage, e.g. self-looseness. In comparison to traditional methods, online monitoring has become more popular and promising in early bolt loosening detection in recent years. As one of the major flaws in bolted connection is looseness, this article aims to briefly review the bolted flange looseness detection in the oil and gas industry.